The figure of Joseph in post-Biblical Jewish literature - Niehoff, Maren. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1992)
This book is a comparative study in the hermeneutics of the ancient interpretations of the biblical Joseph story. Assuming that every interpretation results from a creative encounter between the ultimately open text of Scripture and the specific thought world of the interpreter, it examines the particular way in which each exegete construes the biblical outline of Joseph's character. Paying special attention to the literary nature of the sources, the study begins with an analysis of the narrative methods and the hermeneutic potential of the biblical story, and then proceeds to the inter-testamental evidence. The central concern of this study is to compare the different interpretations of the philosopher Philo, the historian Josephus and the Midrash Genesis Rabbah. These sources do not only range over a considerable amount of time but significantly derive respectively from the Greek and Hebrew cultural realm. Consequently, their figures of Joseph fulfil distinctly different purposes, ranging from an idealisation of Joseph as a Hellenistic politician to autobiographical apologetics and religious instruction.